2013
DOI: 10.1371/journal.pone.0074422
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Preconditioning Protects Rat Liver against Ischemia/Reperfusion Injury by Activating Akt-GSK-3β Signaling and Inhibiting Mitochondrial Permeability Transition

Abstract: Hydrogen sulfide (H2S) is the third most common endogenously produced gaseous signaling molecule, but its impact on hepatic ischemia/reperfusion (I/R) injury, especially on mitochondrial function, remains unclear. In this study, rats were randomized into Sham, I/R, ischemia preconditioning (IPC) or sodium hydrosulfide (NaHS, an H2S donor) preconditioning groups. To establish a model of segmental (70%) warm hepatic ischemia, the hepatic artery, left portal vein and median liver lobes were occluded for 60 min an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 48 publications
5
50
0
Order By: Relevance
“…For many years, H 2 S was considered a toxic agent that causes 85% mortality at high concentrations. Recently, H 2 S has been recognized as being the third inorganic gaseous mediator and can thus infl uence various cellular processes (8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For many years, H 2 S was considered a toxic agent that causes 85% mortality at high concentrations. Recently, H 2 S has been recognized as being the third inorganic gaseous mediator and can thus infl uence various cellular processes (8).…”
Section: Discussionmentioning
confidence: 99%
“…Together, these molecules play a major role in regulating numerous vital biological functions in mammals (7). H 2 S is produced by cystathionine-β-synthase (CBS), cystathionine-γ-lyase (CSE) and 3-mercapto-pyruvate-sulfur-transferase (3MST) in mammalian cells (8). H 2 S is abundantly produced in the kidney and liver (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies suggest that H 2 S potentially regulates the cellular redox balance necessary for the inhibition of oxidative stress and cytoprotection. Supplementation of animals with exogenous forms of H 2 S have demonstrated very robust protection of various organs after ischemia-reperfusion injury, stroke, inflammatory disorders, and models of ischemia-induced angiogenesis (6 -9), atherosclerosis (10), retinopathy (11), hepatic injury (12), and renal dysfunction (13). The molecule is endogenously synthesized from L-cysteine via the action of mainly two enzymes, cystathionine-␥-lyase (CSE) 2 and cystathionine-␤-synthase (CBS) (6).…”
mentioning
confidence: 99%
“…It has been reported that it limits intracellular acidosis, reduces sodium and calcium accumulation into cells (4), and decreases cytolysis and membrane injury caused by oxygen free radicals (5,6). In addition, TMZ conserves mitochondrial function and energy metabolism (7).…”
Section: Introductionmentioning
confidence: 99%